Assessing the ECB's monetary policy stance by comparing tightening cycles - Ignazio Angeloni (Leibniz Institute for Financial Research SAFE, 2024)
In this paper, the ECB monetary policy stance is assessed by comparing the recent tightening cycle (2022-today) with the two preceding ones, which took place in 2000-2001 and in 2006-2008. Interest rates, quantitative indicators and monetary conditions indices (MCIs) are used for this purpose. The main finding is that at the peak of the latest tightening cycle, the ECB monetary policy stance was no more restrictive than it was at the peak of the two preceding ones; actually, probably less. This contrasts with the fact that in the more recent case inflation was higher and more persistent than in the two earlier episodes. This document was provided by the Economic Governance and EMU Scrutiny Unit at the request of the Committee on Economic and Monetary Affairs (ECON) ahead of the Monetary Dialogue with the ECB President on 4 December 2024.
Keywords: 330; ECB Monetary Policy Stance; Tightening Cycle; Inflation